The ABCs of Children's Health Care: How the Medicaid Expansions Affected Access, Burdens, and Coverage between 1987 and 1996 - Jessica S. Banthin; Thomas M. Selden (SAGE Publishing, 2003)
The Medicaid poverty expansions were among the major health policy initiatives of the late 1980s. This paper examines changes over a nine-year period in access, burdens, and coverage among children eligible for Medicaid through the expansions. Among eligible children, the Medicaid expansions reduced rates of uninsurance, increased access to physicians, and reduced families' risk of bearing a heavy financial burden. Gaps remain, however, and expansion-eligible children are more likely than never-eligible children to have been uninsured, to have gone without a physician office visit, and to have lived in a family that spent at least 20% of family income on medical care.